Role of the unfolded protein response, GRP78 and GRP94 in organ homeostasis. Issue 7 (July 2015) - Zhu, Genyuan; Lee, Amy S.
Abstract : The endoplasmic reticulum (ER) is a cellular organelle where secretory and membrane proteins, as well as lipids, are synthesized and modified. When cells are subjected to ER stress, an adaptive mechanism referred to as the Unfolded Protein Response (UPR) is triggered to allow the cells to restore homeostasis. Evidence has accumulated that the UPR pathways provide specialized and unique roles in diverse development and metabolic processes. The glucose regulated proteins (GRPs) are traditionally regarded as ER proteins with chaperone and calcium binding properties. The GRPs are constitutively expressed at basal levels in all organs, and as stress‐inducible ER chaperones, they are major players in protein folding, assembly and degradation. This conventional concept is augmented by recent discoveries that GRPs can be actively translocated to other cellular locations such as the cell surface, where they assume novel functions that regulate signaling, proliferation, apoptosis and immunity. Recent construction and characterization of mouse models where the gene encoding for the UPR components and the GRPs is genetically altered provide new insights on the physiological contribution of these proteins in vivo. This review highlights recent progress towards the understanding of the role of the UPR and two major GRPs (GRP78 and GRP94) in regulating homeostasis of organs arising from the endoderm, mesoderm and ectoderm. GRP78 and GRP94 exhibit shared and unique functions, and in specific organs their depletion elicits adaptive responses with physiological consequences. J. Cell. Physiol. 230: 1413–1420, 2015. © 2014 Wiley Periodicals, Inc., A Wiley Company